2020
DOI: 10.3847/1538-4357/ab91b7
|View full text |Cite
|
Sign up to set email alerts
|

Global Hydromagnetic Simulations of Protoplanetary Disks with Stellar Irradiation and Simplified Thermochemistry

Abstract: Outflows driven by large-scale magnetic fields likely play an important role in the evolution and dispersal of protoplanetary disks and in setting the conditions for planet formation. We extend our 2D-axisymmetric nonideal MHD model of these outflows by incorporating radiative transfer and simplified thermochemistry, with the dual aims of exploring how heating influences wind launching and illustrating how such models can be tested through observations of diagnostic spectral lines. Our model disks launch magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 142 publications
4
93
1
Order By: Relevance
“…Local simulations (Bai & Stone 2013, 2014Bai 2015) found that discs may settle into the slanted symmetry, whether in the ideal MHD regime or not. Although such a configuration would not be physical at large z, as it would imply that one part of the field is bending towards the star, recent global simulations (Bai & Stone 2017;Bai 2017;Béthune et al 2017;Gressel et al 2020) have suggested that in certain radial locations such a symmetry is indeed adopted throughout the vertical extent of the disc region before field lines bend back in the normal manner away from the star further up in the atmosphere. Hence it would be useful to relax the symmetry assumptions of the solution to explore what factors contribute to the disc adopting a particular configuration.…”
Section: Boundary Conditions and Mass Replenishmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Local simulations (Bai & Stone 2013, 2014Bai 2015) found that discs may settle into the slanted symmetry, whether in the ideal MHD regime or not. Although such a configuration would not be physical at large z, as it would imply that one part of the field is bending towards the star, recent global simulations (Bai & Stone 2017;Bai 2017;Béthune et al 2017;Gressel et al 2020) have suggested that in certain radial locations such a symmetry is indeed adopted throughout the vertical extent of the disc region before field lines bend back in the normal manner away from the star further up in the atmosphere. Hence it would be useful to relax the symmetry assumptions of the solution to explore what factors contribute to the disc adopting a particular configuration.…”
Section: Boundary Conditions and Mass Replenishmentmentioning
confidence: 99%
“…By nature of the slanted symmetry, a disc with such configuration cannot (at least in the local model) support a net radial steady state transport of matter or B z flux, as contributions from both sides cancel out. Global simulations (Bai 2017;Béthune et al 2017;Gressel et al 2020;Riols et al 2020) have also shown that such symmetry may lead to a reduction in both overall accretion and flux transport rate, and may even cause the disc wind and accretion stream to be restricted to one hemisphere only. Since the slanted symmetry steady state is more easily reached when the local B z flux is strong, it may contribute to an automatic shut-down mechanism for the flux transport when the local build-up of B z flux becomes too strong and the disc transitions to the slanted state.…”
Section: Implications On Our Understanding Of Protoplanetary Disc Dynmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several routes to enhance the solid-to-gas mass ratio in PPDs either globally or locally. These include magnetized disc winds (Bai 2017;Wang et al 2019;Gressel et al 2020); photoevaporation (Alexander & Armitage 2007;Alexander et al 2014;Wang & Goodman 2017); dusttrapping by pressure bumps (Pinilla et al 2012;Pinilla & Youdin 2017;Dullemond et al 2018); and mutual relative radial drift between dust and gas (Gonzalez et al 2017;Kanagawa et al 2017). It is therefore important to understand how planets interact with dust-rich discs (e.g.…”
Section: Introductionmentioning
confidence: 99%